Role of newly formed platelets in thrombus formation in rat after clopidogrel treatment: comparison to the reversible binding P2Y12 antagonist ticagrelor - Kuijpers, Marijke J. E.; Megens, Remco T. A.; Nikookhesal, Elham; Feijge, Marion A. H.; De Mey, J. G. R.; oude Egbrink, Mirjam G. A.; van Giezen, J. J. J.; Heemskerk, Johan W. M. (Thrombosis and Haemostasis, 2011)
Platelet P2Y12 receptors play an important role in arterial thrombosis by stimulating thrombus growth. Both irreversibly (clopidogrel) and reversibly binding (ticagrelor, AZD6140) P2Y12 antagonists are clinically used for restricted periods, but possible differences in platelet function recovery after drug cessation have not been investigated. We treated WKY rats with a single, high dose of 200 mg/kg clopidogrel or 40 mg/ kg ticagrelor. Blood was collected at different time points after treatment. Flow cytometry confirmed full platelet protection against ADP-induced αIIbβ3 activation shortly after clopidogrel or ticagrelor treatment. At later time points after clopidogrel treatment, a subpopulation of juvenile platelets appeared that was fully responsive to ADP. Addition of ticagrelor to clopidogrel-treated blood reduced αIIbβ3 activation of the unprotected platelets. In contrast, at later time points after ticagrelor treatment, all platelets gradually lost their protection against ADP activation. Perfusion experiments showed abolishment of thrombus formation shortly after clopidogrel or ticagrelor treatment. Thrombus formation on collagen was determined under high shear flow conditions. At later time points, large thrombi formed in the clopidogrel but not in the ticagrelor group, and unprotected, juvenile platelets preferentially incorporated into the formed thrombi. However, platelets from both groups were still similarly reduced in assays of whole blood aggregation. Conclusively, recovery of rat platelet function after ticagrelor differs mechanistically from that after clopidogrel. This difference is masked by conventional platelet aggregation methods, but is revealed by thrombus formation measurement under flow. Juvenile platelets formed at later time points after clopidogrel treatment promoted thrombus formation.
Keywords: Platelet physiology; arterial thrombosis; ADP receptors; pharmacodynamics